Oxidação de enxofre elementar e absorção pelo milho em função de diferentes fertilizantes e doses - Oliveira, Rafael José (2018)
Sulfur is recognized, along with nitrogen, phosphorus and potassium, as an essential nutrient to the development of crops. In agriculture with the use of concentrated fertilizers, high crop extraction due to higher yield, led the fertilizer industries to develop sulfur coated products. Corn (Zea mays L.) is an important crop in many parts of the world, with the United States (34.6%), China (20.8%) and Brazil (9.2%). Considering the above, the objective of this research is to evaluate the efficiency of the absorption of S by maize as a function of the application of elemental sulfur in different doses and sources in maize. The experiments were conducted in greenhouse between november 2016 and july 2017, in the experimental area of the UEG. The hybrid BG7439H was evaluated under entiremently randomized diagram in 4x5 factorial, with four replicates. The first factor was composed by the elemental sulfur coated sources: 1 - urea, 2 - triple superphosphate (TSP), 3 - monoammonium phosphate (MAP), and 4 - elemental sulfur tablets. The second factor was the doses of S (0, 32, 64, 96 and 128 mg dm-3 of soil). The soil was collected in the 0-20 cm layer and passed in the sieve with 2.0 mm mesh. A sample was submitted to chemical and physical analysis. After addition of S- elementar soil samples were incubated for periods of 0, 15, 30, 45 and 60 days, with 60% yours maximum retention capacity of Water. Irrespective of the source of fertilizer supplied, no were observed significant differences for the use of this nutrient by plant. The different sources of sulfur affected characteristics in a similar way and independent of the way the nutrient supplied.